Peran Mediasi Customer Relationship Management: Hubungan Antara Social Media Marketing Terhadap Brand Awareness (Studi Pada Produk Fashion “This Is April” di Kota Malang). - Rahmi, Siti Rafika; Hidayati, Nur; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research is motivated by the rapid growth of the fashion industry driven by technological advances and digitalization, especially through social media as the main marketing platform. This study aims to examine how Customer Relationship Management (CRM) can mediate the impact of Social Media Marketing (SMM) in increasing Brand Awareness. The sample in this study was 100 respondents. The data collection technique in this study used a questionnaire from respondents who used the product "This Is April". This study uses the Structural Equation Modeling-Partial Lest Square (SEM-PLS) method with Smart-PLS software ver. 4.0. The research findings show that the implementation of CRM cannot mediate the effect of SMM on Brand Awareness. However, SMM has a positive and significant influence on Brand Awareness. Keywords: Social Media Marketing, Customer Relationship Management, Brand Awareness.